Speculations about Bystander and Biophotons. Issue 4 (1st October 2014) - Sanders, Charles L.
Mothersill and many others during the last hundred years have shown that cells and now whole animals may communicate with each other by electromagnetic waves called biophotons. This would explain the source of the bystander phenomena. These ultra-weak photons are coherent, appear to originate and concentrate in DNA of the cell nucleus and rapidly carry large amounts of data to each cell and to the trillions of other cells in the human body. The implications of such a possibility can be wonderfully important.